Driving while black : African American travel and the road to civil rights - Sorin, Gretchen Sullivan (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2020)
"How the automobile fundamentally changed African American life-the true history beyond the Best Picture-winning movie. The ultimate symbol of independence and possibility, the automobile has shaped this country from the moment the first Model T rolled off Henry Ford's assembly line. Yet cars have always held distinct importance for African Americans, allowing black families to evade the many dangers presented by an entrenched racist society and to enjoy, in some measure, the freedom of the open road. Gretchen Sorin recovers a forgotten history of black motorists, and recounts their creation of a parallel, unseen world of travel guides, black only hotels, and informal communications networks that kept black drivers safe. At the heart of this story is Victor and Alma Green's famous Green Book, begun in 1936, which made possible that most basic American right, the family vacation, and encouraged a new method of resisting oppression. Enlivened by Sorin's personal history, Driving While Black opens an entirely new view onto the African American experience, and shows why travel was so central to the Civil Rights movement"--